Enabling Students to Communicate in the Target Language in an English Language Class (Tejganga Darpan, 2026)
This study has explored the role of pedagogical practices for students’ reluctance to communicate in the target language in an English language class. It deploys observation and the semi-structured interview as the tools of information collection. Thematic analysis was used for the interpretation and the meaning making. Six students studying in grade 12 in a campus of Panauti were selected as the participants purposively. Interpretivism underpins the research paradigm in the study. The study concludes that various factors like learners’ fragile foundation of the target language, lack of basic vocabulary, fear of making mistakes, disparity in focus for teaching language skills, etc. contribute to the learners’ reluctance in communicating in the target language.